Analyzing the Labor Demand of Restaurant Businesses in Luang Prabang City - Vannalar, Vankham (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research paper analyzes the labor demand of restaurant businesses in Luang Prabang City. The study aims to examine the labor demand of restaurant businesses and identify labor-related problems faced by these establishments. The research employed a questionnaire as the primary data collection tool. The population consisted of 64 restaurant business operators in Luang Prabang City. Statistical tools such as frequency and percentage were used to analyze the data obtained from the questionnaires. The results indicate that the current labor demand of restaurant businesses is primarily for service workers. A total of 46 restaurant businesses, accounting for 71.9%, reported the need for additional labor to meet customer demand. Therefore, businesses must expand their operations to better serve customers and plan additional labor requirements more efficiently to improve service quality. In terms of professional knowledge, entrepreneurs showed a high demand for skills in management, food science, economics and finance, and hotel management. Regarding labor-related issues, 40 restaurant businesses (62.5%) reported experiencing problems, with the most common issues being employees’ lack of punctuality, lack of responsibility for assigned tasks, low work efficiency, and insufficient knowledge of computer use or modern technology to support business operations.